2017
DOI: 10.1111/jzo.12491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different salinities on the osmoregulatory capacity of Mediterranean sticklebacks living in freshwater

Abstract: Three‐spined sticklebacks (Gasterosteus aculeatus L.) of the Camargue region (Rhone delta, northern Mediterranean Sea) occupy coastal mesohaline lagoons and freshwater canals. In this study, the acclimation capacity to different salinities of a population living in freshwater canals was investigated. Freshwater (FW; 5 ‰) individuals were compared to fish acclimated for at least 2 weeks to brackish water (BW; 15 ‰) and seawater (SW; 30 ‰). Blood osmotic pressure and gill Na+/K+‐ATPase (NKA) gene expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…This study also observed ionocytes on the gill lamellae of the FW Asian sea bass, all of which were flat type I. Similarly, a large number of wavy‐convex (flat) type ionocytes were found on the gill lamellae in FW‐acclimated euryhaline fish (Duffy et al, 2011; Kang et al, 2017; Rind et al, 2017). This phenomenon is one of the mechanisms of reversible gill remodeling, in which ionocytes proliferate from the interlamellar epithelium up onto the lateral surface of the lamellae (Wood & Eom, 2021).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This study also observed ionocytes on the gill lamellae of the FW Asian sea bass, all of which were flat type I. Similarly, a large number of wavy‐convex (flat) type ionocytes were found on the gill lamellae in FW‐acclimated euryhaline fish (Duffy et al, 2011; Kang et al, 2017; Rind et al, 2017). This phenomenon is one of the mechanisms of reversible gill remodeling, in which ionocytes proliferate from the interlamellar epithelium up onto the lateral surface of the lamellae (Wood & Eom, 2021).…”
Section: Discussionsupporting
confidence: 59%
“…Lee et al (1996) This study also observed ionocytes on the gill lamellae of the FW Asian sea bass, all of which were flat type I. Similarly, a large number of wavy-convex (flat) type ionocytes were found on the gill lamellae in FW-acclimated euryhaline fish (Duffy et al, 2011;Kang et al, 2017;Rind et al, 2017). This phenomenon is one of the mechanisms of reversible gill remodeling, in which ionocytes proliferate from the F I G U R E 7 Average number of NKA immunoreactive cells (ionocytes) in the interlamellar epithelium of gill filaments (the length of each filament in the longitudinal section containing 15 pairs of lamellae) in SW, BW20, BW10, and FW groups as well as the cells on five lamellae in the FW group of Asian sea bass.…”
Section: Protein Abundance and Specific Activity Of Nkasupporting
confidence: 57%
“…As seen in the European seabass Dicentrarchus labrax and in sticklebacks, in SW a higher gene expression of the branchial NKA α1b isoform occurs compared to the NKA α1a isoform, these isoforms being involved in ion secretion in the SW‐type ionocytes and in ion uptake in the FW‐type ionocytes, respectively (Blondeau‐Bidet et al ., 2016; Rind et al ., 2018). At the protein level, NKA activity is higher in FW fish compared to SW fish.…”
Section: Discussionmentioning
confidence: 99%
“…The plastic boxes contained inorganic sediments (previously burnt at 500 °C for 5 h) and aerated American Standards for Testing and Materials (ASTM) medium. 42 Four solutions were made to prepare the ASTM medium: solution 1, 0.0381 g/L calcium bicarbonate (NaHCO 3 ); solution 2, 0.04914 g/L magnesium sulfate (MgSO 4 •7H 2 O); solution 3, 0.0016 g/L potassium chloride (KCl); solution 4, 0.0024 g/L calcium sulfate (CaSO 4 •2H 2 O). 200 mL was used from each solution 1, 2 and 3 and later 1.5 L of solution 4 in 20 L distilled water, pH 7.5.…”
Section: Test Organism: C Xanthusmentioning
confidence: 99%